KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MODEL PEMBELAJARAN INQUIRI TERBIMBING DAN MEANS ENDS ANALYSIS - Yenny Puspita Sari; Masri Masri (Universitas Muhammadiyah Bengkulu, 2020)
In this research aims to see the difference of mathematical problem solving students with Guided Inquiry learning model and Means Ends Analysis (MEA) learning model. This research was a quasi-experimental research in SMPN 14 Kota Bengkulu. The population of this research is all of VIII class students, with the sample of research is VIII I class as the experimental class I that given using guided inquiry model treatment, students of class VIII 3 as the experimental class II that given Means Ends Analysis model treatment, students of class VIII 2 as the control class that given conventional model treatment. The data collection of students result study using mathematical problem solving skills test consists of pre-test and post-test. The data obtained were analyzed using one path ANAVA and continued with BNT test. Based on the ANAVA result there is a difference between students' mathematical problem solving abilities in experimental class I, experimental class II and control class. From the BNT test that the treatment between experimental class I given the Guided Inquiry, Experimental class II treatment given the Means Ends Analysis Â treatment no difference in mathematical problem solving ability, while experimental class I (Guided Inquiry) with control and experimental class II Means Ends Analysis with the control there is a difference in problem solving abilities mathematically and the highest average score was obtained in the students treated with the Guided Inquiry model.Â Keywords : Ability of Mathematical Problem Solving Students, Guided Inquiry Model, Means Ends Analysis Model